PERBANDINGAN CAMPURAN MEDIA TUMBUH DAN BERBAGAI KONSENTRASI ATONIK UNTUK PERTANAMAN BIBIT (Eucalyptus pellita) - Suhaila Suhaila; Siti Zahrah; Sulhaswardi Sulhaswardi (DINAMIKA PERTANIAN, 2013)
The objective of this research was to know the effect of the mixed grow medya and various atonic concentrations on seed growth of Eucalyptus pellita. The research was conducted at the R and D Nursery of PT. Arara Abadi from October to Desember 2012. The completely randomized design was used with two factors, namely Medya (M) and 5 treatments. The atonic concentration (A) consisted of 4 treatments. The first factor M0 (peat + charcoal husk; 3 : 1), M1 (charcoal husk + cocopeat + compost; 1 : 1 : 1), M2 (charcoal husk + cocopeat + compost; 2 : 1 : 1), M3 (charcoal husk + cocopeat + compost; 1 : 2 : 1), and M4 (charcoal husk + cocopeat + compost; 1 : 1 : 2). The second factor was atonic application (A) with concentration of 0, 2, 4, and 8 cc per liter water. The observed parameters were plant height, number of leaves, stalk diameter, root lenght, root volume and compactness, plant bomass, grow percentage, and seed quality. The results showed that intereacion of mixed medya comparion and atonic application had no a significant effect on the obsrved parameters. The significant effect of medya was found on plant height, stalk diameter, grow percentage, and seed quaity with the best treatment was M4. The atonik application had no a significant effect on plant height, number of leaves, root volume, grow percentage and seed quallity, but had a significant effect on stalk diameter and root lenght.